The transition of cannabis into the mainstream of Australian healthcare: framings in professional medical publications - Monique Lewis; John Flood (BMC, 2021)
Abstract Background Medicinal cannabis has been legalised for use for a range of specified medical conditions in Australia since 2016. However, the nature of the government regulations and the subsequent complexity of prescribing, as well as doctors' safety uncertainties and the stigma of the plant, remain contributing barriers to patient access. Media representations can offer insights into the nature of the discourse about new medical products and therapies and how ideas and understandings about social phenomena become constructed. Focusing on professional medical publications, this study sought to investigate how medicinal cannabis is being represented in professional medical publications. Methods Using a content analysis approach, we investigated articles about medicinal cannabis from 2000 to the end of 2019 in the Medical Journal of Australia, Australian Doctor, Medical Observer, Australian Journal of General Practice, Australian Family Physicia n, and Australian Medicine. Articles were coded according to article type, framings of cannabis, headline and article tone, and key sources used in the article. We also used manifest textual analysis to search for word frequencies, and specific conditions referred to in the articles retrieved. Results A total of 117 articles were retrieved for analysis, the majority of which were news stories for a physician audience. Across the longitudinal period, we found that most reports carried a positive tone towards medicinal cannabis. Cannabis is most frequently framed as a legitimate therapeutic option that is complex to prescribe and access, does not have a strong evidence base to support its use, and also carries safety concerns. At the same time, the outlook on cannabis research data is largely positive. Primary sources most frequently used in these reports are peer-reviewed journals or government reports, voices from medical associations or foundations, as well as government and university researchers. Chronic pain or pain were the conditions most frequently mentioned in articles about cannabis, followed by epilepsy, cancer or cancer pain, and nausea and chemotherapy. Conclusions This analysis offers evidence that medicinal cannabis is being framed as a valid medicine advocated by the community, with potential for addressing a range of conditions despite the lack of evidence, and a medicine that is not free of risk.